2015
DOI: 10.1016/j.stem.2015.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Polycomb Regulates Mesoderm Cell Fate-Specification in Embryonic Stem Cells through Activation and Repression Mechanisms

Abstract: Polycomb complexes (PRC1 and PRC2) are essential regulators of epigenetic gene silencing in embryonic and adult stem cells. Emerging evidence suggests that the core subunit composition regulates distinct biological processes, yet little is known about the mechanistic underpinnings of how differently composed Polycomb complexes instruct and maintain cell fate. Here we find that Mel18, also known as Pcgf2 and one of six Pcgf paralogs, uniquely regulates PRC1 to specify mesoderm cell fate in embryonic stem cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
124
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(135 citation statements)
references
References 46 publications
11
124
0
Order By: Relevance
“…Recently, Mel18, a subunit of PRC1 was shown to impact on mesoderm differentiation by directly controlling the expression of transcription factors essential for early cardiac mesoderm cell specification. 48 Still, many open questions remain as to how PRCs regulate transcription during cardiomyogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Mel18, a subunit of PRC1 was shown to impact on mesoderm differentiation by directly controlling the expression of transcription factors essential for early cardiac mesoderm cell specification. 48 Still, many open questions remain as to how PRCs regulate transcription during cardiomyogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our data and a previously published report showing the importance of PRC1 in cardiac mesoderm differentiation 48 we decided to focus on the role of Zrf1 in cardiac differentiation. First we analyzed specific signaling genes important for cardiogenic mesoderm induction, which represents the first step of cardiomyogenesis (Fig.…”
Section: Zrf1 Controls the Temporal Expression Of Cardiomyogenesis Spmentioning
confidence: 99%
“…Blocking of Pcgf2 up-regulates the expression of the WNT/TCF target Jagged1, a Notch ligand, and consequently activates the Notch pathway [304]. PCGF2 represses pluripotency genes, lineage specification genes, late cardiac differentiation genes, and negative regulators of the Bmp pathway but positively regulates expression of key mesoderm transcription factors (Tbx5, Tbx20, Nkx2.5, Mixl1 and Myl7) during cardiac differentiation due to direct activation of several mesoderm specific genes (Gata4, Hand1, Lhx1 and Six2) [305]. Pcgf2/Mel18 depletion by two specific shRNAs suggested that the protein is not necessary to the self-renewal of ES cells and required for the stability of PHC1 and CBX7 proteins [305].…”
Section: Ncprc12 and Ncprc14mentioning
confidence: 99%
“…PCGF2 represses pluripotency genes, lineage specification genes, late cardiac differentiation genes, and negative regulators of the Bmp pathway but positively regulates expression of key mesoderm transcription factors (Tbx5, Tbx20, Nkx2.5, Mixl1 and Myl7) during cardiac differentiation due to direct activation of several mesoderm specific genes (Gata4, Hand1, Lhx1 and Six2) [305]. Pcgf2/Mel18 depletion by two specific shRNAs suggested that the protein is not necessary to the self-renewal of ES cells and required for the stability of PHC1 and CBX7 proteins [305]. Genome wide ChIP coupled massive parallel sequencing analysis of PCGF2/MEL18 binding sites in during cardiac differentiation of ES cells revealed that PCGF2 has two antagonistic functions.…”
Section: Ncprc12 and Ncprc14mentioning
confidence: 99%
See 1 more Smart Citation